2011
DOI: 10.1007/s10103-011-0900-7
|View full text |Cite
|
Sign up to set email alerts
|

Diode laser (808 nm) applied to oral soft tissue lesions: a retrospective study to assess histopathological diagnosis and evaluate physical damage

Abstract: The diode laser is today widely used in oral pathology to excise lesions; however, some controversy surrounds laser surgery, specifically the accuracy of pathological diagnosis and the control over thermal tissue damage. This study aimed to establish if physical damage induced by the diode laser could affect the histopathological diagnosis and to evaluate the damage caused to the resection margins. Between 2005 and 2010, at S. Gerardo Hospital, Milan, 608 cases of soft tissue lesions localized in the oral cavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
62
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 19 publications
0
62
0
3
Order By: Relevance
“…10 However, more tissue damage occurs than with the use of a scalpel, 19 but this damage is not prejudicial to the specimen tissue, specially when the specimens contained a diameter of at least 5 mm. 11 In the current study, the tissue damage was minimal, and only one lesion was measured at 5 mm in diameter. In addition, the LASER characteristics and settings, such as power output, wavelength, emission modalities, type of optical fiber, and affinity with target tissues can control the width and severity of the thermal damage caused to the tissue.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…10 However, more tissue damage occurs than with the use of a scalpel, 19 but this damage is not prejudicial to the specimen tissue, specially when the specimens contained a diameter of at least 5 mm. 11 In the current study, the tissue damage was minimal, and only one lesion was measured at 5 mm in diameter. In addition, the LASER characteristics and settings, such as power output, wavelength, emission modalities, type of optical fiber, and affinity with target tissues can control the width and severity of the thermal damage caused to the tissue.…”
Section: Discussionmentioning
confidence: 67%
“…In addition, the LASER characteristics and settings, such as power output, wavelength, emission modalities, type of optical fiber, and affinity with target tissues can control the width and severity of the thermal damage caused to the tissue. 11 By contrast, diode LASER surgery provides a thermal damage zone of less than 1mm, which allows for surgical precision and excellent hemostasis within a dry operative field. 20,21 Hemostasis caused by LASER surgery is due to the increase in platelet activation at the end point of the wound, which leads to the sealing of the blood vessels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 However, diode lasers also showed to be advantageous in excision of soft tissue. 36 Aras et al reported the comparison between diode laser and Er:YAG. Results indicated that Er:YAG could be performed without local anesthetic injection.…”
Section: Discussionmentioning
confidence: 99%
“…Os autores concluíram que não há interferência no resultado do exame histológico, independentemente da técnica utilizada, desde que a lesão seja maior que 7 mm. Já para Angiero et al 17 , que também estudaram os danos causados pelo uso do laser na remoção de lesões em tecido mole e a sua interferência na análise histológica, a lesão deve ter no mínimo 5 mm para que os danos não interfiram nesse tipo de diagnóstico.…”
Section: Discussionunclassified